Association between single nucleotide polymorphisms in prospective genes and susceptibility to ankylosing spondylitis and inflammatory bowel disease in a single centre in Turkey - Küçükşahin, Orhan; Ateş, Aşkın; Türkçapar, Nuran; Törüner, Murat; Turgay, Murat; Duman, Türker; Şahin, Ali; Yıldızgören, Mustafa Turgut; Okoh, Alexis K.; Külahçıoğlu, Emre; et al. (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: To establish the prevalence of the single nucleotide polymorphisms (SNPs) of endoplasmic reticulum aminopeptidase 1 (ERAP1), IL-23 receptor (IL-23R), signal transducer and activator of transcription 3 (STAT-3) and Janus kinase 2 (JAK-2) in ankylosing spondylitis (AS) and inflammatory bowel disease (IBD) in a Turkish population. Materials and Methods: A total of 562 subjects who presented at the Ankara University internal medicine departments of rheumatology and gastroenterology outpatient clinics were recruited in this study, including 365 patients with AS, 197 patients with IBD and 230 healthy controls. ERAP1, IL-23R, STAT-3 and JAK-2) were genotyped in competitive allele-specific polymerase chain reactions. Results: The ERAP1 (rs26653) polymorphism was found to increase the disease risk in patients with AS and IBD compared with the control group (p=0.02 and p=0.01, respectively). In addition, this polymorphism revealed a significant relationship with the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and the Bath AS Functional Index (BASFI) in patients with AS (r=0.829, p<0.001 and r=0.731, p<0.001, respectively). Conclusion: The ERAP1 gene polymorphism might be a risk factor in the pathogenesis of AS and IBD. In contrast, IL-23R gene polymorphisms may serve a protective role in AS and IBD.